Singlet Fission from Upper Excited Electronic States of Cofacial Perylene Dimer - Ni, Wenjun; Gurzadyan, Gagik G; Zhao, Jianzhang; Che, Yuanyuan; Li, Xiaoxin; Sun, Licheng (The journal of physical chemistry letters, 2019)
Singlet fission directly from the upper excited vibrational and electronic states of cofacial perylene dimers, bypassing the relaxed state S , was detected within 50 fs. This process competes well with vibrational cooling in S (4.7-7.0 ps) and S → S internal conversion (380 fs). The singlet fission has the energy threshold E = 3.06 eV. Other competitive relaxation processes are excimer and dimer cation formation on an ultrafast time scale. Excitation to higher energy levels (4.96 eV) leads to a higher efficiency of singlet fission.